Coming of Age for Autotaxin and Lysophosphatidate Signaling: Clinical Applications for Preventing, Detecting and Targeting Tumor-Promoting Inflammation - Benesch, Matthew G.K. (Cancers (Basel), 2018)
A quarter-century after the discovery of autotaxin in cell culture, the autotaxin-lysophosphatidate (LPA)-lipid phosphate phosphatase axis is now a promising clinical target for treating chronic inflammatory conditions, mitigating fibrosis progression, and improving the efficacy of existing cancer chemotherapies and radiotherapy. Nearly half of the literature on this axis has been published during the last five years. In cancer biology, LPA signaling is increasingly being recognized as a central mediator of the progression of chronic inflammation in the establishment of a tumor microenvironment which promotes cancer growth, immune evasion, metastasis, and treatment resistance. In this review, we will summarize recent advances made in understanding LPA signaling with respect to chronic inflammation and cancer. We will also provide perspectives on the applications of inhibitors of LPA signaling in preventing cancer initiation, as adjuncts extending the efficacy of current cancer treatments by blocking inflammation caused by either the cancer or the cancer therapy itself, and by disruption of the tumor microenvironment. Overall, LPA, a simple molecule that mediates a plethora of biological effects, can be targeted at its levels of production by autotaxin, LPA receptors or through LPA degradation by lipid phosphate phosphatases. Drugs for these applications will soon be entering clinical practice.